Peran Roh Kudus Bagi Pertumbuhan Rohani Orang Kristen - Hidayati, Ermin; Kisuk, Choi (STT KINGDOM BALI, 2024)
God longs for every Christian who has accepted Jesus as Lord and Savior to step into the next journey, namely experiencing spiritual growth. This journey is not natural, but supernatural, where understanding and experience with the Holy Spirit will bring about spiritual growth. Exploring the role of the Holy Spirit through the Gospel of John 14 and 16 is an early indication of the life of a Christian growing towards Christlikeness